IMF Policies and Practices on Capacity Development. (Policy Papers; Policy Paper ;, 2019)
This statement summarizes the IMF's policies and practices with regard to the delivery of capacity development (CD) activities. It updates the 2014 Statement on IMF Policies and Practices on Capacity Development and reflects the conclusions of the 2018 Review of the Fund's Capacity Development Strategy, approved by the Executive Board on November 14, 2018. The purpose of the statement is to consolidate the guiding principles endorsed by the Board with policies and practices that are within the authority of IMF's management and are followed by staff in carrying out capacity development activities. The statement is expected to be of use to IMF staff, Executive Directors and their staff, country authorities, and donors. It also serves as a point of reference for future reviews of the IMF's CD activities.